Seasonal variation in Importance Value Index (IVI), Diversity Indices and Biomass of aquatic macrophytes at Biratnagar and adjoining areas, eastern Nepal - Niroula, Bhabindra; Singh, KLB (Nepalese Journal of Biosciences, 2013)
Aquatic macrophytes of three freshwater bodies of Biratnagar and adjoining areas in eastern Nepal namely, Betana-a natural oxbow pond, Bhattapokhari-an aged derelict depression, and Singhia river were analysed for their importance value index (IVI), diversity indices and biomass seasonally from January 2008 to December 2009. Singhia river had high species richness-d (2.08-3.84) and Shannon Wienner index-H' (2.16-2.68). Betana pond and Bhattapokhari had low diversity indices; however, nutrient rich Bhattapokhari had highest primary productivity (2675.5 g/m2/yr) in comparison to Betana pond (303.7 g/m2/yr) and Singhia river (479.09 g/m2/yr). Seasonally vittates dominated Betana pond had IVI range between 6.3 and 258.8 and biomass range between 168.1±7.3 and 265.8±38.7 g/m2); pleustophytes dominated Bhattapokhari had IVI range between 41.6 and 192.8 and biomass range between 925.5±353.2 and 2020.02±213.1 g/m2), and hyperhydate dominated Singhia river had IVI ranged between 2.5 and 160.9 and biomass ranged between 120.7±55.8 and 283.5±28.3 g/m2. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7462 Nepalese Journal of Biosciences 1: 1-7 (2011)